Validation of weather based forewarning model for Helicoverpa armigera in chickpea - SAGAR, D; NEBAPURE, SURESH M; CHANDER, SUBHASH (The Indian Journal of Agricultural Sciences, 2019)
Weather based forewarning model for Helicoverpa armigera developed earlier was validated by recording the activity of H. armigera through pheromone trap catches in chickpea sown during rabi 2017–18 at IARI, New Delhi. The moth activity of H. armigera commenced in 52nd SMW (last week of December) and peak trap catch was during 15th SMW with 183moths/trap/week in April. The male moth population had significant positive and very strong correlation with maximum temperature (r=0.816**) and minimum temperature (r=0.820**) of 1-lag week and significant negative correlation with morning (r=-0.774**) and evening relative humidity (r=-0.655**) of 1-and 2-lag week respectively. The repeatability of model accuracy to predict the H. armigera adult population was validated satisfactorily (R2 = 0.719, RMSE=1.66%, MBE=-0.71% and MAE=1.26%) with 2017–18 weather data and H. armigera trap catches.